PENGARUH PENERIMAAN SURAT PEMBERITAHUAN PAJAK TERHUTANG (SPPT), TINGKAT KEPERCAYAAN KEPADA PEMERINTAH, SIKAP, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UNTUK MEMBAYAR PAJAK BUMI DAN BANGUNAN - I Made Seta Umbaran; Kadek Dewi Padnyawati; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2022)
This study aims to investigate the effectiveness of tax returns payment revenue (SPPT), the level of trust toward the government, attitudes, and tax sanctions on taxpayer compliance to pay property taxes in Pering Sari Village, Selat District, Karangasem Regency. The population in this study were all 3501 householder who were registered as recepients of the 2020 Land and Building Tax Return Payment in Selat District, Pering Sari Village. There were 100 respondents selected as samples in this study through Slovin formula, probability sampling, and simple random sampling. The data was collected through questionnaire, and further being analyzed using multiple linear regression model and being calculated with the assistance of SPSS. This study resulted in there was a significant effect of tax return payment revenue, level of trust to the government, tax sanctions toward taxpayer compliance to pay land and building taxes. The coefficient of determination resulted in 53.8% of the taxpayer compliance was influenced by variations in SPPT revenue, level of trust to the government, attitudes, and tax sanctions while the rest of 46.2 percent was determined by extraneous factors that were not included in this study.